2015
DOI: 10.1177/1479164115588545
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of serum response factor in podocyte epithelial–mesenchymal transition of diabetic nephropathy

Abstract: Together, increased serum response factor activity provokes podocytes' epithelial-mesenchymal transition and dysfunction in diabetic nephropathy. Targeting serum response factor by small-molecule inhibitor may be an attractive therapeutic strategy for diabetic nephropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 31 publications
1
8
1
Order By: Relevance
“…The lifespan of Mkl1/Mkl2 dKO mice was over 10 weeks, slightly longer than Srf KO mice. Previous studies showed an injury-promoting role of SRF/MKL in kidney disease [25][26][27][28] ; in contrast, data here support SRF and MKL1/MKL2 in the maintenance of normal podocyte structure and function.…”
Section: Significance Statementcontrasting
confidence: 54%
“…The lifespan of Mkl1/Mkl2 dKO mice was over 10 weeks, slightly longer than Srf KO mice. Previous studies showed an injury-promoting role of SRF/MKL in kidney disease [25][26][27][28] ; in contrast, data here support SRF and MKL1/MKL2 in the maintenance of normal podocyte structure and function.…”
Section: Significance Statementcontrasting
confidence: 54%
“… 31 α-SMA is a useful cytoskeletal biomarker of EMT, which has been detected in the fibrotic process of various organs undergoing EMT. 32 34 TGF-β is an inducer of EMT and initiates EMT by regulating transcriptional, posttranscriptional, translational, and posttranslational levels. 35 Increased TGF-β expression has been linked to EMT in renal fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…These methods were described previously. 15 All primer sequences are reported in Table 1. siRNA and luciferase assay SRF siRNA (5 0 -GACCTGCCTCAACTCGCCAGAC-3 0 ) was described previously. 16 786-O cells were transfected with the pcDNA 3.1 or pcDNA-SRF plasmid and non-specific siRNA or SRF siRNA along with empty vector or pGL3-Snail plasmid using HiPerFect Transfection Reagent (Qiagen, Hilden, Germany).…”
Section: Plasmids and Transfection Quantitative Rt-pcr Western Blotmentioning
confidence: 99%